The Effect Of E-Training Towards Employee Performance - ismail, fadillah (Research in Management of Technology and Business, 2022)
A well trained and groomed employee will be able to gain some competitive advantages for the organization when the employee is fully equipped with needed skills and talents. Upgrading the skills of an employee is important as it can be use during the time of survival of organization towards any challenges that may arise. Work balance is when an employee able to work effectively and efficiently and in the same time able to deal with personal problems. Unfortunately, organization that does not think of the work balance of their own employees which will affecting the employee productivity and also the employee performance. Therefore, this study attempt to identify the level and effect of E-training on employee performance at Venture Technocom Sdn Bhd., Kami Electronics (M) Sdn. Bhd., Sharp Manufacturing Corporation (M) Sdn. Bhd., Escatec Mechatronics Sdn. Bhd., Johor. Quantitative research method is used to collect 80 data from the respondents among employees in human resources and general management department through online survey questionnaire. The results show that the variables were not significant to each other. The study recommended that E-Training to be implemented in Manufacturing sector for a positive impact on the employee performance by having variety of platform of E-Training.